The pros and cons of sick pay schemes: Testing for contagious presenteeism and shirking behavior - Stefan Pichler; Nicolas Ziebarth (W.E. Upjohn Institute for Employment Research, 2015)
This paper proposes a test for the existence and degree of contagious presenteeism and negative externalities in sickness insurance schemes. First, we theoretically decompose moral hazard into shirking and contagious presenteeism behavior and derive testable conditions. Then, we implement the test exploiting German sick pay reforms and administrative industry-level data on certified sick leave by diagnoses. The labor supply adjustment for contagious diseases is significantly smaller than for noncontagious diseases. Lastly, using Google Flu data and the staggered implementation of U.S. sick leave reforms, we show that flu rates decrease after employees gain access to paid sick leave.
Keywords: I12; I13; I18; J22; J28; J32; 330; Sickness Insurance; Paid Sick Leave; Presenteeism; Contagious Diseases; Infections; Negative Externalities; Shirking; United States; Germany